Discovery learning model to optimize students’ critical thinking skills on hydrocarbon material - Tesa Lonika Yuniawati; Friska Juliana Purba (Pascasarjana Universitas Negeri Medan, 2021)
Learning in 21st century requires an advance human mindset, especially critical thinking skills. Critical thinking skills improve the learning process to be more optimal in taking the core of the learning. However, data shows that the critical thinking skills of class XI IPA 2 students are still lacking because they have not been able to answer the analytical questions which is this is the important skills for the students. This paper aims to describe the use of discovery learning models to optimize students' critical thinking skills. The research method used is descriptive qualitative. The research subjects were 28 students of class XI IPA 2 in one of the senior high schools in Jakarta in the academic year 2021/2022 odd semester. Based on the study and data on each indicator, it was found that the use of discovery learning models was able to optimize students' critical thinking skills. Each step in the discovery learning model facilitates the achievement of indicators of critical thinking skills. Keywords: Critical thinking, discovery learning, learning in 21st century